One-pot three-component route for the synthesis of S-trifluoromethyl dithiocarbamates using Togni’s reagent - Halimehjani, Azim Ziyaei; Dračínský, Martin; Beier, Petr (Beilstein Journal of Organic Chemistry, 2017)
A one-pot three-component route for the synthesis of S-trifluoromethyl dithiocarbamates by the reaction of secondary amines, carbon disulfide and Togni’s reagent is described. The reactions proceed in moderate to good yields. A similar reaction using a primary aliphatic amine afforded the corresponding isothiocyanate in high yield. A variable temperature NMR study revealed a rotational barrier of 14.6, 18.8, and 15.9 kcal/mol for the C–N bond in the dithiocarbamate moiety of piperidine, pyrrolidine, and diethylamine adducts, respectively. In addition, the calculated barriers of rotation are in reasonable agreement with the experiments.
Keywords: dithiocarbamates; electrophilic trifluoromethylation; Togni reagents

(untitled) - Marinovich, M.; Viviani, B.; Capra, V.; Corsini, E.; Anselmi, L.; D’Agostino, G.; Di Nucci, A.; Binaglia, M.; Tonini, M.; Galli, C. L. (Chem. Res. Toxicol., 2002)

(untitled) - Malik, A. K.; Rao, A. L. J. (J. Agric. Food Chem., 2000)

(untitled) - Weissmahr, K. W.; Houghton, C. L.; Sedlak, D. L. (Anal. Chem., 1998)

(untitled) - Sugimoto, H.; Makino, I.; Hirai, K. (J. Org. Chem., 1988)

(untitled) - Maddani, M.; Prabhu, K. R. (Tetrahedron Lett., 2007)

(untitled) - Das, P.; Kumar, C. K.; Kumar, K. N.; Innus, M.; Iqbal, J.; Srinivas, N. (Tetrahedron Lett., 2008)

(untitled) - Wong, R.; Dolman, S. J. (J. Org. Chem., 2007)

(untitled) - Guillaneuf, Y.; Couturier, J.-L.; Gigmes, D.; Marque, S. R. A.; Tordo, P.; Bertin, D. (J. Org. Chem., 2008)

(untitled) - Ziyaei Halimehjani, A.; Maleki, H.; Saidi, M. R. (Tetrahedron Lett., 2009)
and references therein.

(untitled) - Grainger, R. S.; Welsh, E. J. (Angew. Chem., Int. Ed., 2007)

(untitled) - Ahmed, S.; Baker, L. A.; Grainger, R. S.; Innocenti, P.; Quevedo, C. E. (J. Org. Chem., 2008)

(untitled) - McMaster, C.; Bream, R. N.; Grainger, R. S. (Org. Biomol. Chem., 2012)

(untitled) - Lai, J. T.; Shea, R. (J. Polym. Sci., Part A: Polym. Chem., 2006)

(untitled) - Nieuwenhuizen, P. J.; Ehlers, A. W.; Haasnoot, J. G.; Janse, S. R.; Reedijk, J.; Baerends, E. J. (J. Am. Chem. Soc., 1999)

(untitled) - Imamura, H.; Ohtake, N.; Jona, H.; Shimizu, A.; Moriya, M.; Sato, H.; Sugimoto, Y.; Ikeura, C.; Kiyonaga, H.; Nakano, M.; Nagano, R.; Abe, S.; et al. (Bioorg. Med. Chem., 2001)

(untitled) - Scozzafava, A.; Mastorlorenzo, A.; Supuran, C. T. (Bioorg. Med. Chem. Lett., 2000)

(untitled) - Hou, X.; Ge, Z.; Wang, T.; Guo, W.; Cui, J.; Cheng, T.; Lai, C.; Li, R. (Bioorg. Med. Chem. Lett., 2006)

(untitled) - Azizi, N.; Aryanasab, F.; Saidi, M. R. (Org. Lett., 2006)

(untitled) - Ziyaei-Halimjani, A.; Saidi, M. R. (Can. J. Chem., 2006)

(untitled) - Ziyaei Halimehjani, A.; Zanussi, H. P.; Ranjbari, M. A. (Synthesis, 2013)

(untitled) - Ziyaei Halimehjani, A.; Marjani, K.; Ashouri, A. (Green Chem., 2010)

(untitled) - Azizi, N.; Aryanasab, F.; Torkiyan, L.; Ziyaei, A.; Saidi, M. R. (J. Org. Chem., 2006)

(untitled) - Ziyaei Halimehjani, A.; Hajiloo Shayegan, M.; Hashemi, M. M.; Notash, B. (Org. Lett., 2012)

(untitled) - Chaturvedi, D.; Ray, S. (Tetrahedron Lett., 2006)

(untitled) - Charpentier, J.; Früh, N.; Togni, A. (Chem. Rev., 2015)

(untitled) - Václavík, J.; Zschoche, R.; Klimánková, I.; Matoušek, V.; Beier, P.; Hilvert, D.; Togni, A. (Chem. – Eur. J., 2017)

(untitled) - Ismalaj, E.; Le Bars, D.; Billard, T. (Angew. Chem., Int. Ed., 2016)

(untitled) - Zhang, C. (ARKIVOC, 2014)

(untitled) - Shibata, N.; Matsnev, A.; Cahard, D. (Beilstein J. Org. Chem., 2010)

(untitled) - Niedermann, K.; Früh, N.; Vinogradova, E.; Wiehn, M. S.; Moreno, A.; Togni, A. (Angew. Chem., Int. Ed., 2011)

(untitled) - Bertrand, F.; Pevere, V.; Quiclet-Sire, B.; Zard, S. Z. (Org. Lett., 2001)

(untitled) - Matoušek, V.; Václavík, J.; Hájek, P.; Charpentier, J.; Blastik, Z. E.; Pietrasiak, E.; Budinská, A.; Togni, A.; Beier, P. (Chem. – Eur. J., 2016)

(untitled) - Ashirbaev, S. S.; Levin, V. V.; Struchkova, M. I.; Dilman, A. D. (J. Fluorine Chem., 2016)

(untitled) - Kitazume, T.; Sasaki, S.; Ishikawa, N. (J. Fluorine Chem., 1978)

(untitled) - Chniti, I.; Sanhoury, M. A. K.; Merlet, D.; Chehidi, I. (J. Fluorine Chem., 2014)

(untitled) - Wessel, W.; Tyrra, W.; Naumann, D. (Z. Anorg. Allg. Chem., 2001)

(untitled) - Scattolin, T.; Klein, A.; Schoenebeck, F. (Org. Lett., 2017)

(untitled) - Pontes, R. M.; Basso, E. A.; dos Santos, F. P. (J. Org. Chem., 2007)

(untitled) - Holloway, C. E.; Gitlitz, M. H. (Can. J. Chem., 1967)